High-Resolution Qualitative and Quantitative Magnetic Resonance Evaluation of the Glenoid Labrum. Issue 6 (November 2015) - Iwasaki, Kenyu; Tafur, Monica; Chang, Eric Y.; Statum, Sheronda; Biswas, Reni; Tran, Betty; Bae, Won C.; Du, Jiang; Bydder, Graeme M.; Chung, Christine B.
Abstract : Objective: This study aimed to implement qualitative and quantitative magnetic resonance sequences for the evaluation of labral pathology. Methods: Six glenoid labra were dissected, and the anterior and posterior portions were divided into normal, mildly degenerated, or severely degenerated groups using gross and magnetic resonance findings. Qualitative evaluation was performed using T1-weighted, proton density-weighted, spoiled gradient echo and ultrashort echo time (UTE) sequences. Quantitative evaluation included T2 and T1rho measurements as well as T1, T2*, and T1rho measurements acquired with UTE techniques. Results: Spoiled gradient echo and UTE sequences best demonstrated labral fiber structure. Degenerated labra had a tendency toward decreased T1 values, increased T2/T2* values, and increased T1rho values. T2* values obtained with the UTE sequence allowed for delineation among normal, mildly degenerated, and severely degenerated groups ( P < 0.001). Conclusions: Quantitative T2* measurements acquired with the UTE technique are useful for distinguishing among normal, mildly degenerated, and severely degenerated labra.